IMPLEMENTASI PROGRAM PEMBATASAN KUNJUNGAN RUTAN SEBAGAI PENCEGAHAN COVID-19 DI JEPARA (Studi Kasus di Rumah Tahanan Kelas IIB Jepara) - ERVANI SETIAWAN, GABRIELLA; Rostyaningsih, Dewi; Hanani, Retna (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The overcrowded conditions of correctional institutions and detention centers have made it challenging to enforce social distancing rules and are highly susceptible to the transmission and spread of the Covid-19 virus. In response, a new policy program to limit visits to detention centers as a prevention of Covid-19 in Jepara has been implemented. This qualitative research describes and analyzes the visit restriction program at the Class IIB Detention Center in Jepara as a strategic measure to prevent the spread of the Covid-19 virus. The program includes face-to-face visits, safekeeping of goods and food, and mechanisms for receiving complaints. The analysis shows that the policy's implementation is running well, with proper infrastructure and adequate support. However, challenges such as expensive telephone kiosks and non-transparent packaging for goods and food have been identified. The research suggests continued compliance with basic rules to control the pandemic and making adjustments to address the identified challenges.